Microstructure and paramagnetic Meissner effect of YBa2Cu3Oy nanowire networks - Pessoa, A. L. [UNESP]; Koblischka-Veneva, A.; Carvalho, C. L. [UNESP]; Zadorosny, R. [UNESP]; Koblischka, M. R. (My University, 2020)
The microstructure and magnetic characterizations of non-woven, fabric-like YBa2Cu3Oy (YBCO) nanofiber mats are reported. The samples were produced by solution blow spinning (SBS), starting from a sol-gel solution of the precursor materials in polyvinylpyrrolidone. In the present work, the nanowire network samples were morphologically characterized by scanning electron microscopy, and the superconducting properties were measured by magnetometry. An interesting feature is the appearance of a paramagnetic Meissner effect (PME) when field-cooling, firstly verified in that sort of sample. The PME appears only in very small applied magnetic fields, which is similar to previous observations of the PME on an artificially granular YBCO thin film, but distinctly different from bulk samples investigated in the literature. Thus, we explain the PME by flux trapping within the voids of the nanoporous structure of the nanofiber mats. [Figure not available: see fulltext.].
Keywords: Paramagnetic Meissner effect; Solution blow spinning; YBCO nanofiber mats